Optimized selection of dopant solvents for improving the sequential doping efficiency of conjugated polymers - Yoon, Sang Eun; Han, Ji Min; Seo, Bo Eun; Kim, Sang Wook; Kwon, O. Pil; Kim, Bong Gi; Kim, Jong H. (Organic Electronics, 2021)
Molecular doping for conjugated polymers is an important tool for modifying their electrical and optical properties, which extends conjugated polymer's application to various optoelectronic devices. Sequential doping, i.e., dopant diffusion into a pre-deposited polymer film is one of the most widely used molecular doping methods. To improve dopant diffusion efficiency, solvent engineering for conjugated polymers has been studied, however, less attention has been given to solvent selection for the dopant, which is equally important as dopant carriers. In this study, we suggest a selection rule for dopant solvents in the application of sequential doping based on the systemic characterizations of Hansen solubility parameters, UV–Vis absorption spectra, and electrical conductivity. Furthermore, by applying the rule to different conjugated polymers, we demonstrate the wide applicability of our findings on dopant solvent selection.
Keywords: Doping efficiency; Electrical and optical properties; Electrical conductivity; Hansen solubility parameters; Molecular doping; Optimized selection; Solvent engineering; Solvent selection; Conjugated polymers; Doping efficiency; Sequential doping; Solubility; Solvents